Kinetic Aspects of the Electrochemical Reduction of Uranyl in HCl Solutions. Issue 1 (21st January 2022) - Muñoz, Andrés G.; Weiss, Stephan
Abstract : The interfacial mechanism of uranyl electroreduction at Au-electrodes in HCl solutions was discussed on the light of systematic studies of cyclovoltammetry, normal pulse voltammetry, UV–vis spectroscopy and published electroanalytical research. Voltammetric waves were numerically deconvoluted on the basis of a reaction model consisting of a first mass-controlled, quasi-reversible first electron transfer and a subsequent reduction of interfacial U(V) intermediate species with adsorption of generated U(IV) products. The dependence of the kinetic parameters on [HCl] indicates an electron transfer following an inner-sphere type mechanism assisted by electrosorption of chloride ligands. The interfacial accumulation of chloride exerts a strong electrostatic repulsion of complexed uranyl and a consequent edged drop of electron transfer rates at [HCl] ∼ 0.5 mol l −1 . The electron transfer steps are followed by a chemical desorption reaction of the unstable tetravalent uranyl in U(H2 O)9 4+ species. It is shown that the numerical reproduction of voltammetric waves suits as a method for calculating kinetic parameters in multi-steps electrochemical reactions.